Yazilim tanimli a?lar için OMNeT++ platformunda OpenFlow protokolünün benzetimi - Aksoy, Faruk; Das, Resul (Institute of Electrical and Electronics Engineers Inc., 2019)
Software Defined Network (SDN) is a network structure designed to provide effective solutions to adaptation, configuration, scalability and management problems encountered in traditional network structures. Because of its flexible architecture, ease of management and centralized control, softwaredefined networks are replacing traditional networks. The routing rules are transferred from the control plane to the data plane. Openflow is the most common protocol used by the control plane. In this article, using the OMNeT ++ simulation platform, the simulations of the most commonly used openflow protocol in software-defined networks with modules created in NED language are simulated. The performance of the openflow protocol was monitored as a result of the application. The size of the data packets received and transmitted during the communication between the control and data planes and the resulting traffic load can be considered as a disadvantage in software defined networks. © 2019 IEEE.
2019 International Conference on Artificial Intelligence and Data Processing Symposium, IDAP 2019 -- 21 September 2019 through 22 September 2019 -- Malatya -- 153040
Keywords: OMNeT++; openflow; SDN; Software defined networks